2001
DOI: 10.1073/pnas.98.2.445
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage/polyadenylation factor IA associates with the carboxyl-terminal domain of RNA polymerase II in Saccharomyces cerevisiae

Abstract: The carboxyl-terminal domain (CTD) of the largest subunit of RNA polymerase II plays an important role in transcription and processing of the nascent transcript by interacting with both transcription and RNA processing factors. We show here that the cleavage͞ polyadenylation factor IA of Saccharomyces cerevisiae directly contacts CTD. First by affinity chromatography experiments with yeast extracts we demonstrate that the Rna15p, Rna14p, and Pcf11p subunits of this complex are associated with phosphorylated CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 42 publications
5
117
0
1
Order By: Relevance
“…4A), which prefers the phosphorylated form of the CTD [157,172,173]. The crystal structure of Pcf11p in complex with a phosphorylated CTD peptide has been reported (Fig.…”
Section: Hpcf11 (Pcf11p)mentioning
confidence: 96%
See 1 more Smart Citation
“…4A), which prefers the phosphorylated form of the CTD [157,172,173]. The crystal structure of Pcf11p in complex with a phosphorylated CTD peptide has been reported (Fig.…”
Section: Hpcf11 (Pcf11p)mentioning
confidence: 96%
“…Additionally, yeast CTD interacts with Cft2p/Ydh1p and Pcf11p [118,172,173,213] and the mammalian CTD binds CstF-50 [85]. Protein binding generally increases upon phosphorylation of the CTD, and 3′-end processing is stimulated in vitro by phosphorylated CTD [215].…”
Section: The Ctd Of Poliimentioning
confidence: 99%
“…Ser2 phosphorylated CTD helps to recruit and/or stabilize polyadenylation factors, thereby facilitating coupling of transcription and mRNA 39-end formation. For instance, in yeast, Ser2 phosphorylation of the CTD potentiates interaction with the essential polyadenylation factor Pcf11 (de Vries et al 2000;Barilla et al 2001;Licatalosi et al 2002;Ahn et al 2004). The H3-K36 methyltransferase Set2 binds elongating RNAPII, recognizing the doubly phosphorylated CTD (Ser5/Ser2) (Hampsey and Reinberg 2003;Kizer et al 2005).…”
Section: Ctd Of the Rnapii Large Subunitmentioning
confidence: 99%
“…For example, the C-terminal domain (CTD) of the RNAPII largest subunit also plays an important role in 39-end processing, likely by mediating interactions with 39-end processing factors (McCracken et al 1997;Hirose and Manley 1998;Barilla et al 2001;Fong and Bentley 2001). The Paf1 complex (Paf1C), which was first identified in yeast as an elongation factor and plays a role in transcription-associated chromatin modification (Krogan et al 2002;Squazzo et al 2002;Simic et al 2003;Mueller et al 2004;Rozenblatt-Rosen et al 2005), has been shown to be involved in mRNA 39-end formation (Penheiter et al 2005;Rosonina and Manley 2005) by interacting with CPSF, CstF, and symplekin (Nordick et al 2008;Rozenblatt-Rosen et al 2009).…”
Section: -End Processing Machinerymentioning
confidence: 99%
“…The 3'-end processing factors can bind to the CTD affinity column (McCracken et al, 1997). Furthermore, several factors, including Pcf11, Pta1, and Rna14 show an apparent preference for binding to the phosphorylated CTD (Rodriguez et al, 2000;Barilla et al, 2001;Licatalosi et al, 2002;Meinhart and Cramer, 2004). In particular, the yeast 3'-end processing factors appear to be recruited in time through the phosphorylation of S2 of the CTD when pol II approaches the 3'-end of a gene.…”
Section: Deciphering the Ctd Codementioning
confidence: 99%